Analisis Hukum Terhadap Penggabungan Dan Pemisahan Perkara Pidana Dalam Surat Dakwaan Penuntut Umum - Christina Mahdalena Saragih; Sonya Airini Batubara; Martin Johan Napitupulu; Nico Iryanto Sihombing; Novita Wanrelin Gultom (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This article aims to analyze the consideration of the public prosecutor in merging and separating indictments for several criminal cases and to find out the obstacles of the public prosecutor in merging and separating indictments against several criminal cases. The research used is normative juridical research. With secondary research methods, namely secondary legal materials, which consist of books and articles related to research (both in the form of newspapers, magazines, journals, and other writings). The data obtained are then analyzed qualitatively by describing and describing the data and facts resulting from a research in the field with an interpretation, evaluation, and general knowledge. In the results of this study, the merger of indictments against several criminal cases is Article 141 of the Criminal Procedure Code which reads: "Public prosecutors can merge cases and make them into one indictment". Meanwhile, for the separation of the indictment, there is Article 142 of the Criminal Procedure Code which reads: "In the event that the Public Prosecutor receives a case file containing several criminal acts committed by several suspects which are not included in the provisions of Article 141"